Answer:
8
Step-by-step explanation:
This one is similar to the other one done with graphs , the only difference is we have equations instead of graphs.
Like the other one, we want to find f(2) and whatever that equals we plug into g(x) to find g(f(2))
So first lets find f(2)
f(x) = x - 4
f(2) = 2 - 4
f(2) = -2
g(f(2)) , f(2) = -2 , g(-2)
now lets find g(-2)
g(x) = -2x + 4
g(-2) = -2(-2) + 4
multiply -2 and -2 to get 4
g(-2) = 4 + 4
add 4 and 4 to get 8
g(-2) = 8
We can conclude that g(f(2)) = 8
The answer is 68 because if it rose between the times it would mean you minus 7 from 75
Let Cameron be x years old now.
-
<u>Now:</u>
Cameron = x
Uncle =3x
-
<u>4 years ago:</u>
Cameron = x - 4
Uncle = 3x - 4
-
<u>4 years ago, Uncle is 4 times older:</u>
3x - 4 = 4(x - 4)
-
<u>Find x:</u>
3x - 4 = 4(x - 4)
3x - 4 = 4x - 16
4x - 3x = 16 - 4
x = 12
-
<u>Find the age:</u>
Cameron = x = 12
-
Answer: Cameron is 12 years old now.
Pretty sure the answer is 18
3^2+3^2=9+9=18 (with a square root)